A reduction and pH dual-sensitive polymeric vector for long-circulating and tumor-targeted siRNA delivery - Li, Jingguo (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.